2004
DOI: 10.1152/ajpheart.01210.2003
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathological role of TNF-α in early cardiac dysfunction and subsequent heart failure after infarction in rats

Abstract: A marked increase in plasma TNF-alpha has been described in patients with chronic heart failure (CHF). Nevertheless, little is known about the direct role of this cytokine early after myocardial infarction (MI) and its possible effects on the subsequent development of CHF. Wistar rats were subjected to permanent in vivo coronary artery ligation. At 5, 7, and 9 days after MI, cardiac function, passive compliance of the left ventricle (LV), and cardiac geometry were evaluated. The same model was used to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 36 publications
(38 reference statements)
5
53
0
1
Order By: Relevance
“…However, the roles of TNF-␣ in MI remain controversial. Blockade of TNF-␣ has been reported to be both beneficial (1,15,24,26,27) and deleterious (2,18,22). In the present study, we evaluated the pathophysiological roles of two distinct cell surface receptors (TNFR1 and TNFR2) in the process of infarct healing and cardiac remodeling after MI.…”
Section: Discussionmentioning
confidence: 97%
“…However, the roles of TNF-␣ in MI remain controversial. Blockade of TNF-␣ has been reported to be both beneficial (1,15,24,26,27) and deleterious (2,18,22). In the present study, we evaluated the pathophysiological roles of two distinct cell surface receptors (TNFR1 and TNFR2) in the process of infarct healing and cardiac remodeling after MI.…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition studies have produced contradictory findings regarding the effects of TNF-α neutralization on the infarcted heart. Several studies demonstrated injurious effects of TNF-α signaling in mediating infarct expansion [153], and cardiac dysfunction [154]. On the other hand, other investigations indicated protective effects of TNF-α signaling in the infarcted myocardium.…”
Section: Tnf-αmentioning
confidence: 99%
“…Irwin et al (10) have extended these data by showing that TNF-␣ mRNA and protein are persistently expressed by myocytes in the noninfarcted regions of the myocardium from 1 day to 5 wk after coronary artery ligation. Finally, we have demonstrated that the TNF-␣ protein is transiently overexpressed 7 days after infarction in rats and that the inhibition of this cytokine reduces cardiac alterations and improves the long-term prognosis of MI (2). Nevertheless, these observations were made on an extreme experimental model in which infarction was obtained by permanent ligation of the left coronary artery, inducing massive and transmural necrosis of the LV free wall.…”
mentioning
confidence: 98%